Intelligent motion of rocker-bogie mechanism for amphibious vehicle - Zakariya bin Zainol (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Emergency management (pre-disaster occurrence) and first response information (post-disaster occurrence) are crucial during disaster attack as time is of the essence of life. The study in this field is vital especially in Malaysia, which located in the south-east Asia region, within the link of the natural disaster area. It is of prime important for this research to come out with an intelligent amphibious vehicle that can be used on both land and water to monitor and provide alerts in emergency management and glides through disaster area during the post-disaster occurrence. This thesis presented the development of an amphibious vehicle for disaster relief which is named as (SOPHIBIAN). It has the capability to manoeuvre intelligently with real-time control and obstacle avoidance capability on land, muddy places and in water. Sensors detecting devices are included in hardware implementation to be used for terrain mapping and global tracking within the disaster area. In this research, a thorough study of an amphibious vehicle design is conducted to enhance its amphibious capability by considering float ability, stability and resistance/propulsion characteristics and its performance during a water crossing operation. A rocker-boogie hardware mechanism is proposed for a smooth manoeuvring transition between land and water surfaces. The artificial bee colony (ABC) algorithm is used and has been successfully adopted as an intelligent technique for obtaining optimised PID controller gain parameters for the motor current control analysis of SOPHIBIAN vehicle. The classical control approach using PID control does not achieve satisfactory results in controlling the system where it has resulted in longer response rise time and settling-time whereas the ABC optimised method has shown good control performance in input tracking as opposed to the conventional method.